Al-Quran Sebagai Motor Penggerak Peradaban Dunia yang Paling Menakjubkan - Hajjin Mabrur (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2020)
Al-Qur'an states itself as a human changer, both individual and communal, who brings people from darkness to bright light (QS. Ibrohim [14]: 1). The historical reality is related to the statement of the Al-Qur'an above that transformative al-Qur'an in building human civilization can be observed from the reality of Arab society which directly feels the presence of the verses of the al-Qur'an. There are stark contrasts in the Arab region, especially regarding the development of society between before and after the Qur'an was revealed. Before the Qur'an was revealed, the Arabs were nothing more than a community called jahiliyah. It consists of tribes that are predominantly nomadic, hostile to each other, far from knowledgeable, and left behind in the cultural field of the surrounding nations. However, after the Qur'an was revealed and Islam was broadcast, the conditions of the Arabs gradually changed and progressed. Arabs who had been divided and hostile to each other became